2004
DOI: 10.1177/0022002703262358
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Political Violence on Tourism

Abstract: The hypothesis that political violence deters tourism is mainly based on case study evidence and a few quantitative studies confined to a small sample of countries. Two estimation techniques—a fixed-effects panel estimator with contemporaneous effects only and a dynamic generalized method of moments estimator—are used to test the impact of various forms of political violence on tourism. Both models show strong evidence that human rights violations, conflict, and other politically motivated violent events negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
266
1
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(297 citation statements)
references
References 23 publications
12
266
1
18
Order By: Relevance
“…The fundamental difference between a terrorist campaign and a civil war is that the former does not hold and manage territory within a nation state. 6 The ICRG internal conflict index is also used in a large number of studies on political stability (e.g., Gupta et al, 2004;Jinjarak, 2009;Bjorvatn and Farzanegan, 2013, 2015, Long, 2008Neumayer, 2004;Lessmann, 2016). We have also examined our hypothesis by using an objective measure of conflict, namely, the maxintyearv413 variable in the UCDP Monadic Conflict Onset and Incidence Dataset (Themnér andWallensteen, 2014 andGleditsch et al, 2002).…”
Section: Dependent Variable: Political Stability (Stab_icrg)mentioning
confidence: 99%
“…The fundamental difference between a terrorist campaign and a civil war is that the former does not hold and manage territory within a nation state. 6 The ICRG internal conflict index is also used in a large number of studies on political stability (e.g., Gupta et al, 2004;Jinjarak, 2009;Bjorvatn and Farzanegan, 2013, 2015, Long, 2008Neumayer, 2004;Lessmann, 2016). We have also examined our hypothesis by using an objective measure of conflict, namely, the maxintyearv413 variable in the UCDP Monadic Conflict Onset and Incidence Dataset (Themnér andWallensteen, 2014 andGleditsch et al, 2002).…”
Section: Dependent Variable: Political Stability (Stab_icrg)mentioning
confidence: 99%
“…While research by Neumayer in 2004, concluded that political violence including terrorism incident, human rights violation and bank's violent events consistently has a negative impact on tourism arrivals since tourist naturally are sensitive to events of political violence in their holiday destination because such event jeopardize a relaxed and unconcerned holiday [15].…”
Section: Safety and Security In Tourism Industriesmentioning
confidence: 99%
“…Because tourism is a labor-intensive industry, many job activities are related to the supply chain of the sector such as food delivery services, production and sale of handicrafts, recreational activities, and construction of tourism infrastructures (United Nations World 588 YAP AND SAHA 2006;Neumayer, 2004;Sönmez, 1998); however, whether terrorism and corruption will affect tourists' decisions to travel still remains puzzling. Tourists in modern days would prefer new travel experience particularly to those Third World destinations that may have considerably high level of corruption but may not necessarily be politically unstable.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial that a demand model should incorporate political risk indicators that evidently play a significant influence on tourism businesses (e.g., Hoti, McAleer, & Shareef, 2007;Neumayer, 2004), especially in countries that contain UNESCO-listed heritage. The model not only aims to generate accurate tourism forecasts but also to give correct estimations of the long-term financial commitments to rebuild and sustain heritage tourism in highly political unstable countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation